Standardised quantitative radioiodine SPECT/CT Imaging for multicentre dosimetry trials in molecular radiotherapy. (19th December 2019) - Gregory, Rebecca A; Murray, Iain; Gear, Jonathan; Leek, Francesca; Chittenden, Sarah; Fenwick, Andrew; Wevrett, Jill; Scuffham, James; Tipping, Jill; Murby, Brian; Jeans, Steve; Stuffins, Martha; et al.
Abstract: The SEL-I-METRY trial (EudraCT No 2015-002269-47) is the first multicentre trial to investigate the role of 123 I and 131 I SPECT/CT-based tumour dosimetry to predict response to radioiodine therapy. Standardised dosimetry methodology is essential to provide a robust evidence-base for absorbed dose–response thresholds for molecular radiotherapy (MRT). In this paper a practical standardised protocol is used to establish the first network of centres with consistent methods of radioiodine activity quantification. Nine SPECT/CT systems at eight centres were set-up for quantitative radioiodine imaging. The dead-time of the systems was characterised for up to 2.8 GBq 131 I. Volume dependent calibration factors were measured on centrally reconstructed images of 123 I and 131 I in six (0.8–196 ml) cylinders. Validation of image quantification using these calibration factors was performed on three systems, by imaging a 3D-printed phantom mimicking a patient's activity distribution. The percentage differences between the activities measured in the SPECT/CT image and those measured by the radionuclide calibrator were calculated. Additionally uncertainties on the SPECT/CT-based activities were calculated to indicate the limit on the quantitative accuracy of this method. For systems set-up to image high 131 I count rates, the count rate versus activity did not peak below 2.8 GBq and fit a non-paralysable model. The dead-times and volume-dependent calibration factors were comparable between systems of the same model and crystal thickness. Therefore a global calibration curve could be fitted to each. The errors on the validation phantom activities' were comparable to the measurement uncertainties derived from uncertainty analysis, at 10% and 16% on average for 123 I and 131 I respectively in a 5 cm sphere. In conclusion, the dead-time and calibration factors varied between centres, with different models of system. However, global calibration factors may be applied to the same system model with the same crystal thickness, to simplify set-up of future multi-centre MRT studies.